2021
DOI: 10.1186/s13002-021-00441-4
|View full text |Cite
|
Sign up to set email alerts
|

Traditional food plants of the upper Aswa River catchment of northern Uganda—a cultural crossroads

Abstract: Background In the parkland agroforestry system of northern Uganda, smallholder farming households rely on a diversity of plant species to fulfil their nutritional requirements, many of which also serve a range of medicinal, cultural, and livelihood functions. The purpose of the study was to assemble an inventory of indigenous plant species used as food in four districts within the Aswa River catchment of northern Uganda, and to document their utilization and management by rural communities. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 22 publications
1
5
0
Order By: Relevance
“…The bark mucilage consumption of G. mollis was previously reported only by the studies conducted in Bullen district, northwest Ethiopia [ 36 ] and in the Amaro Special District of southern Ethiopia [ 34 ], while the fruit edibility was highly described by other studies [ 11 , 14 , 23 , 32 ] in the country. In other African countries, a ripe fruit is edible in Uganda [ 63 ], a bark mucilage is used as an additives in local cake preparation, and a bark powder is used to improve the texture of foods in Nigeria [ 64 ]. This shows the vital attributes of G. mollis in traditional food preparations and fighting against food insecurity in Ethiopia as well as in Africa.…”
Section: Resultsmentioning
confidence: 99%
“…The bark mucilage consumption of G. mollis was previously reported only by the studies conducted in Bullen district, northwest Ethiopia [ 36 ] and in the Amaro Special District of southern Ethiopia [ 34 ], while the fruit edibility was highly described by other studies [ 11 , 14 , 23 , 32 ] in the country. In other African countries, a ripe fruit is edible in Uganda [ 63 ], a bark mucilage is used as an additives in local cake preparation, and a bark powder is used to improve the texture of foods in Nigeria [ 64 ]. This shows the vital attributes of G. mollis in traditional food preparations and fighting against food insecurity in Ethiopia as well as in Africa.…”
Section: Resultsmentioning
confidence: 99%
“…In the ethnomedicinal perspective, leaves and stems of A. flagellaris were reported to be used against gonorrhea and syphilis in Nigeria [23], its fruits for eye diseases, and its roots for measles in Uganda [24]. Leaves of B. antidysenterica were used to treat wounds in Zuway Dugda district [25] and diarrhea surrounding the Gullele Botanic Garden in central Ethiopia [26].…”
Section: Discussionmentioning
confidence: 99%
“…Parkland agroforestry is an indigenous land use system developed by farmers which allows them to grow annual crops in combination with useful trees and shrubs which are scattered cultivated fields at varying densities (Boffa, 1999;Masters, 2021). In addition to cereals, farmers draw on a rich legacy of ethnobotanical knowledge to selectively retain native trees within fields and farmland that provide a range of medicinal, cultural, and livelihood functions.…”
Section: Parkland Agroforestry West Africamentioning
confidence: 99%
“…In addition to cereals, farmers draw on a rich legacy of ethnobotanical knowledge to selectively retain native trees within fields and farmland that provide a range of medicinal, cultural, and livelihood functions. For example, Masters (2021) found that parklands systems of four cultures occupying the Aswa River catchment of northern Uganda included 88 indigenous edible plants used as sources of leafy vegetables, roots and tubers, fruits, oils, and seeds.…”
Section: Parkland Agroforestry West Africamentioning
confidence: 99%